Formulation and Evaluation of Azithromycin Dihydrate Solid Dispersion with Esther of Polyethylene Glycol-6000 and Stearic Acid Using A Co-Grinding Technique - Mardiyanto; Budi Untari; Ady Mara; Nauval Hady Prasetyo (Science and Technology Indonesia, 2023)
Azithromycin is a narrow-spectrum bacterial growth inhibitory antibiotic derived from macrolides with low dissolution in water. Several methods have been carried out to increase the dissolution of medicinal substances, one of which is solid dispersion. Solid dispersions are mixtures consisting of one or more active substances in an inert carrier. The purpose of this study was to determine the effect of formatting solid dispersions with PEG 6000 polymer and stearic acid on increasing the dissolution rate of azithromycin. The method of formatting solid dispersions uses the co-grinding method. Solid dispersion of azithromycin was prepared in four formulas with variations in the amount of PEG 6000. Tests carried out on solid dispersion samples of azithromycin were XRD, FTIR, SEM, solubility tests, and dissolution tests. Test results on azithromycin solid dispersions prepared by co-grinding showed that there was an effect of the amount of PEG 6000 on decreasing the intensity of azithromycin crystals, there was no chemical interaction between azithromycin and the carrier, differences in the morphology of pure azithromycin powder and solid dispersions, and an increase in the dissolution of solid dispersions in medium SIF.